Psychological distress experienced by parents caring for an immunosuppressed child during the COVID-19 pandemic. (May 2023) - Driessens, Corine; Mills, Lynne; Patel, Ravin; Culliford, David; Gbesemete, Diane; Lee, Emma; Shaunak, Meera; Chappell, Harry; Faust, Saul N.; de Graaf, Hans; ,
Abstract: The COVID-19 pandemic has proved unique in both its unpredictability and the extent to which it has continued to impact on daily life since March 2020. Among the immunosuppressed population the challenges of the COVID-19 pandemic are cumulative to the ever-present challenges of living with a long-term condition. This prospective longitudinal study explored patterns of concern experienced by 467 British parents caring for an immunosuppressed child during the first 2 years of the COVID-19 pandemic and related this to parental mental wellbeing. Most parents slowly adapted or were resilient to the ever-changing stressors of the COVID-19 pandemic. However, 12% experienced high levels of concern throughout the first 2 years of the pandemic. This group was also more likely to report emotional mental health problems towards the end of this period. The experience of emotional mental health problems among parents caring for an immunosuppressed child was related to low household income, single parenting, difficult access to greenspace, and higher level of exposure to COVID positive cases and COVID restrictions (North of England). Parents reported that optimism, reduction of isolation, and support promoted coping and management of the challenges of the COVID-19 pandemic. More reliable COVID information and periodic medical-condition-specific guidance would have been appreciated. These findings can increase clinical awareness of high-risk parental groups and make an important contribution to the planning of appropriate targeted psychological family interventions. Highlights: Parental psychological response followed a resilient, recovery, or enduring psychological distress pathway. Optimism, reduced social isolation, and informational support seemed to mitigate the experience of psychological distress. Perceived infection risk, uncertainty, social media use and lack of guidance appeared to increase psychological distress. Following an enduring psychological distress pathway increased parental likelihood to experience health problems.